Cost Evaluation of Irinotecan‐Related Toxicities Associated With the UGT1A1*28 Patient Genotype. Issue 1 (20th March 2017) - Roncato, R; Cecchin, E; Montico, M; De Mattia, E; Giodini, L; Buonadonna, A; Solfrini, V; Innocenti, F; Toffoli, G
Abstract : The adoption of a preemptive UGT1A1*28 genotyping to increase irinotecan safety in clinical practice is still limited. This is the first actual study of costs associated with the management of irinotecan‐related toxicities, and their association with UGT1A1*28 genotype. A retrospective analysis of the cost of toxicity management was conducted on 243 metastatic colorectal cancer patients enrolled in a clinical trial and treated with standard of care FOLFIRI (5‐fluorouracil combined with irinotecan). The mean predicted cost per patient was higher for *28/*28 (€4, 886), vs. *1/*1 (€812), (regression coefficient 1.79, 95% confidence interval (CI) = 1.31–2.28; P < 0.001) and for *1/*28 (€1, 119) vs. *1/*1 (regression coefficient 0.32, 95% CI = 0.04–0.60; P  = 0.024). This is consistent with a different grade 4 toxicity profile among the three genotypes, and a higher frequency of costly interventions like hospitalization among patients with the *28 allele. A differential toxicity management cost by *28 genotype is herein demonstrated, representing a first step towards the demonstration of the test clinical utility.